2014
DOI: 10.1161/circulationaha.113.007839
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Acute Retrograde Type A Aortic Dissection With an Entry Tear in Descending Aorta

Abstract: Background-Optimal management strategy of acute aortic dissection (AD) with retrograde extension from entry tear in the descending aorta into the ascending aorta remains undetermined. Methods and Results-Of the 538 patients who were diagnosed as having acute AD from 1999 through 2011, 49 patients (37 men; 52.5±13.1 years) were identified as having entry tear in the descending aorta with retrograde extension of AD into the ascending aorta. Sixteen patients who were clinically stable with thrombosed false lumen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
53
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 23 publications
3
53
1
Order By: Relevance
“…In addition, although a type A dissection is still an independent risk factor for mortality in patients with spontaneous dissections, 11 our findings are congruent with a recent report by Kim et al, 12 pointing out the fact that an acute retrograde type A aortic dissection presents a more favorable prognosis than antegrade dissections (spontaneous).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, although a type A dissection is still an independent risk factor for mortality in patients with spontaneous dissections, 11 our findings are congruent with a recent report by Kim et al, 12 pointing out the fact that an acute retrograde type A aortic dissection presents a more favorable prognosis than antegrade dissections (spontaneous).…”
Section: Discussionsupporting
confidence: 91%
“…Based on these findings, the data supported the expectation that proximal entry tear occlusion with TEVAR would lead to Editorial Editorial on the article entitled "the impact of intimal tear location and partial false lumen thrombosis in acute type b aortic dissection" FL decompression and subsequent favorable remodeling after ATBAD. Indeed, in a previous study (16) which corroborated the hemodynamic implications of this study along with an earlier report by Kaji et al (17), we showed that acute spontaneous retrograde type A dissection was associated with a more favorable prognosis than aortic dissection with antegrade flow. In this context, the insights provided by Girish et al (1) and the experimental design that was used may serve as a solid foundation for continuing related research that will ultimately help in expanding our understanding and efforts to treat this difficult disease.…”
supporting
confidence: 92%
“…(3) This most often occurs when associated with previous aortic intervention. (3) Other risk factors for acute aortic dissection include hypertension, pregnancy, congenital cardiovascular diseases, inflammatory or infective conditions involving the aorta, connective tissue disorders associated with cystic medial necrosis, and prior trauma or vascular intervention.…”
Section: Discussionmentioning
confidence: 99%
“…(3) This most often occurs when associated with previous aortic intervention. (3) Other risk factors for acute aortic dissection include hypertension, pregnancy, congenital cardiovascular diseases, inflammatory or infective conditions involving the aorta, connective tissue disorders associated with cystic medial necrosis, and prior trauma or vascular intervention. (6,7) A typical clinical presentation includes a history of acute onset of severe chest pain, often with radiation to the back or epigastrium, and is commonly associated with hypertension.…”
Section: Discussionmentioning
confidence: 99%